Evaluation of a new brain tissue probe for intracranial pressure, temperature, and cerebral blood flow monitoring in patients with aneurysmal subarachnoid hemorrhage - Seule, Martin; Sakowitz, Oliver; Santos, Edgar; Orakcioglu, Berk; Unterberg, Andreas (Neurocritical care, 2016)
To evaluate an intraparenchymal probe for intracranial pressure (ICP) and temperature (TEMP) monitoring as well as determination of cerebral hemodynamics using a near-infrared spectroscopy (NIRS) and indocyanine green (ICG) dye dilution method (NIRS-ICP probe).